Iqbal and the Challenge of Reform within the Muslim World - Muzaffar, Chandra (Intellectual Discourse, 2013)
Fundamental to Iqbal’s reconstruction of religious thought was his challenge to Muslims to understand tawhīd and to re-think their entire concept of, and approach to, Islam. He pleaded for the return of the spirit of ijtihād in the interpretation of the law. He was impressed by Western civilization’s passion for self-consciousness, social justice and egalitarianism though he distanced himself from its atheistic strain and from the ideas that were a hindrance to the spiritual and moral advancement of the human being. Iqbal abhorred imperialism, democracy and race-based nationalism. He equally attacked the fossilised religious dogmatism that had sapped the spirit of Islam. Iqbal sketched a blue print of a polity to give life and meaning to tawhidic values.